Analysis Of The Influence Of Spindle Speed And Feed Rate On The Surface Quality Of The CNC Lathe Machining Process Using SS400 Material With Taguchi Method - Sutisna, Nanang Ali; Al Grage, Fathir Fajaryanto (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2025)
The CNC lathe machining process is one of the choices in the manufacturing industry. The CNC lathe machining process usually makes machine components that are either flat or cylindrical. This process has a principle, namely a process of forming the outer and inner surfaces of the material by rotating the workpiece and then meeting it with a cutting tool with an axis parallel to the workpiece. A CNC lathe is a machine that can move a cutting tool by receiving command data and then processing it. This study will show the effect of variations in spindle rotation speed and also variations in feed rate on the CNC Lathe Liouy Hsing 450 machine on the surface quality of the workpiece. In this study, SS400 steel and WNMG-type cutting tools were used as fixed variables, with variations in spindle speed of 800, 1000, and 1200 rev/min and feed rates of 0.1, 0.2, and 0.3 mm/min. The methods that will be used are experiments and statistics, then data collection will be carried out using observation and documentation methods. The data that has been obtained will be processed using Microsoft Excel. This study concluded that feed rate has a greater influence than spindle speed, and the fourth experiment at a spindle speed variation of 1000 rev/min and a feed rate of 0.1 mm/min had the smoothest surface roughness value of 0.487µm.